Pengaruh Komunikasi Formal Terhadap Pengambilan Keputusan Promosi Jabatan Pegawai Di Badan Kepegawaian Daerah - Nur Azizah; Dematria Pringgabayu (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
The problem that becomes the study of this research is about employee promotion decisions. The core of the study focused on the factors that influence employee promotion decisions. One of these factors is communication, namely formal communication. Based on this, the main problem revealed in this study is there any influence of formal communication on employee promotion decisions. The research method used is the descriptive method, with questionnaire data collection techniques on a scale of five Likert categories, to 54 employees who have experienced appointment at the Regional Civil Service Agency of West Java Province. The data analysis technique used is a simple regression test. Based on the calculations obtained by the results of alternative hypotheses stating "There is the Effect of Formal Communication (X) on Employee Promotion Decision Making (Y) in the Regional Civil Service Agency of West Java Province." While the magnitude of the influence of formal communication on employee promotion decisions is equal to 15.60%, the remaining 84.4% influenced by other factors